2011
DOI: 10.1111/j.1365-2982.2011.01740.x
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal ulcer disease, gastroduodenal motor function and reflux esophagitis – a cross‐sectional survey in a subset of Taiwanese patients

Abstract: Presence of erosive esophagitis in a subset of Taiwanese patients with healed DU and negative H. pylori status was associated with slower solid phase gastric emptying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…The enrolled patients were organized to have a scintigraphic measurement of solid phase of GE as described before . After an overnight fast, the patient was asked to drink a 100 cc of distilled water and eat a sandwich, containing a 99mTC‐labeled scrambled egg with a final 300‐g weight and 335‐kcal content meal (35% of fat, 45% of carbohydrate, and 20% of protein) in 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enrolled patients were organized to have a scintigraphic measurement of solid phase of GE as described before . After an overnight fast, the patient was asked to drink a 100 cc of distilled water and eat a sandwich, containing a 99mTC‐labeled scrambled egg with a final 300‐g weight and 335‐kcal content meal (35% of fat, 45% of carbohydrate, and 20% of protein) in 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, the relevant impact of disordered GE on the clinical feature of GERD in the Asian countries remains incomplete . Earlier studies from Asian have reported elderly subjects tend to have slower GE .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation